Synergistic Inhibitory Effect of Biosynthesized ZnO-CuO Nanocomposite on Biofilm Formation of Proteus mirabilis - Faiq, Noor Hamza; Ahmed , Mais E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Proteus mirabilis is considered the third most common cause of catheter-associated urinary tract infections. With urease production, the potency of the catheter’s blockage due to the formation of biofilm is significantly enhanced. This study was aimed at exploring whether green synthesized ZnO-CuO nanoparticles (ZnO-CuO NPs) can function as an anti-biofilm agent produced by P.Mirabilis. The characterization of biosynthesized nanoparticles was carried out to determine the chemical and physical properties of the product using AFM, TEM, FESEM, XRD, and UV visible spectrometry. The hexagonal structure was confirmed by XRD, the size range was marked at 96.00nm by TEM, and FESEM was used to confirm the surface morphology. AFM analysis is used to reveal the roughness and distribution of nanoparticles. UV-visible spectra of the synthesized nanoparticles recorded a maximum peak at 287nm and 232nm. Zinc and Copper nanoparticles showed remarkable biofilm inhibitory effects on wild-type strains of multidrug-resistant Proteus mirabilis.Downregulation changes in LuxS expression using real-time PCR technology were detected after treatment with the ZnO-CuO nanocomposite of these strains. A cytotoxicity test of CuO-ZnO NPs-based nanocomposite showed that this nanocomposite is safe for use, where the IC50 was 161.6 µg/mL. Anti-cancer activity against urethral bladder cancer cell lines was recorded in vitro, where the IC50 was 107.4 µg/mL.